2012
DOI: 10.1001/archdermatol.2012.1830
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors of Paraneoplastic Pemphigus

Abstract: To identify the prognostic factors of overall survival in a series of patients with paraneoplastic pemphigus (PNP).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
2
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(112 citation statements)
references
References 42 publications
3
103
2
4
Order By: Relevance
“…The mortality of patients with PNP is 75% to 90% [3]. However, a recent study conducted in France [99] revealed a mortality of 51%, 59% and 69% in 1, 2 and 5 years, respectively.…”
Section: Associated Tumorsmentioning
confidence: 97%
“…The mortality of patients with PNP is 75% to 90% [3]. However, a recent study conducted in France [99] revealed a mortality of 51%, 59% and 69% in 1, 2 and 5 years, respectively.…”
Section: Associated Tumorsmentioning
confidence: 97%
“…The most common causes of death were infection (n=21) and evolution of neoplasia (n=6). Keratinocyte necrosis on histopathology and erythema multiforme-like skin lesions on clinical exam were associated with a worse prognosis, particularly in the setting of extensive mucocutaneous lesions [62].…”
Section: Paraneoplastic Pemphigusmentioning
confidence: 97%
“…Prognosis is generally considered to be poor with mortality rates of 75-90 % quoted historically [61]. However, a more recent study of 53 patients suggests that these prior numbers may have been inflated due to estimations taken from small series, or case studies which were more likely to have reported the most severe cases [52,62,63]. Their study demonstrated overall 5-year survival rates of 38 % with 1-and 3-year survival rates of 49 and 41 %, respectively.…”
Section: Paraneoplastic Pemphigusmentioning
confidence: 99%
“…Naudoti raktažodžiai: "pemphigus", "autoantibody", "desmogleins", "immunofluorescence", "pemphigus vulgaris", "pemphigus foliaceus", "paraneoplastic pemphigus", "systemic corticosteroids". [3,6,10,13,[16][17][18][19] Pemphigus etiologija ir patogenezė. Pemphigus -tai heterogeniška autoimuninė odos ir gleivinių liga, susijusi su autoantikūnų (autoAk) imunoglobulino G (IgG) ir imunoglobulino A (IgA) gamyba prieš skirtingas adhezijos molekules epidermyje ir pasireiškianti intraepiderminėmis akantolitinėmis pūslėmis.…”
Section: Tyrimo Objektas Ir Metodikaunclassified